PENGARUH MEDIA SOSIAL TIKTOK TERHADAP PENGETAHUAN BAHAYA SEKS BEBAS PADA REMAJA KELAS IX SMPN 6 KOTA BATAM - Elis, Camenyta Fiterina; Saputra, Andi Ipaljri; Mindasari, Hanny (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: Teenagers can learn about sex education from social media, one of the social media platforms that is in great demand by all levels of society is TikTok. Currently, teenagers' needs for obtaining educational information and information services are still not being met well enough. So health promotion is needed to increase knowledge of the dangers of free sex in teenagers. Methods: This research design is experimental research with pretest-posttest. The population and sample in this study were 72 students using the stratified random sampling method, namely random sampling based on class division and data collection techniques using questionnaires. The research was carried out in October 2023 at SMP N 6 Batam. Results: The results showed that there was a significant difference in the level of knowledge between before and after being given health promotion via TikTok social media regarding the dangers of free sex with a p-value of 0.000. Conclusion: Based on the research results, there is an influence of TikTok social media health promotion on teenagers' knowledge about the dangers of free sex at SMP N 6 Batam City. It is hoped that this research will be a reference for conducting further research and it is recommended to research knowledge and attitudes.